Investigation of Crystal Size Distribution in Purification of Terephthalic Acid from Polyester Textile Industry Waste by Reactive Crystallization - Bekti Marlena; Hary Sulistyo; Rochmadi Rochmadi (Universitas Gadjah Mada, 2023)
The purification of terephthalic acid recovered from an alkali-reduction wastewater by reactive crystallization was investigated. The crude terephthalic acid was reacted with sodium hydroxide solution to form a salt of disodium terephthalate, then acidified with sulfuric acid to get the terephthalic acid with higher purity. Effects of time, pH, concentration, and flow rate of secondary feed solutions, temperature, and stirring rate on Crystal Size Distribution (CSD) of terephthalic acid precipitate were investigated. The results showed that CSD was influenced by the concentration of reactants and the pH solution. On the other hand, time, temperature, flow rate of secondary solution, and stirring rate had no significant effects on the CSD, which the mean size of crystals ±3 μm. The mean size of crystals at solution pH 5, 4, and 3 were 6.03, 9.42, and 10.34 μm, respectively; meanwhile, at concentrations of 0.5, 0.3, and 0.1 M, were 7.57, 3.24, and 3.09 μm, respectively. The semi-batch reactive crystallization with double-feeding at constant pH and temperature produced monodispersed crystals. However, this method needs to be carried out more than once for terephthalic acid purification, which is intended for polyethylene terephthalate (PET) polymerization.